Antibody Responses to Respiratory Syncytial Virus: A Cross-Sectional Serosurveillance Study in the Dutch Population Focusing on Infants Younger Than 2 Years. (23rd September 2020) - Berbers, Guy; Mollema, Liesbeth; van der Klis, Fiona; den Hartog, Gerco; Schepp, Rutger
Abstract: Background: Respiratory syncytial virus (RSV) generally causes mild disease but can cause severe infections in (premature) infants and elderly adults. Here, we studied RSV-specific antibody concentrations throughout life with emphasis on infants and chronic obstructive pulmonary disease (COPD) patients. Methods: Sera (N = 2655) from 2 nationwide cross-sectional studies in the Netherlands including individuals aged 0–90 years were analyzed for IgG and IgA antibodies to RSV prefusion F, postfusion F, N, Ga, and Gb proteins and for antibody avidity in 42 COPD patients. Results: Maternal IgG concentrations declined to age 10–12 months. After the first year of life, approximately 40% of children lacked infection-induced IgA antibodies and may therefore be uninfected. All Dutch children showed serological evidence of RSV infection by age 3 years. Antibody concentrations reached a plateau by age 5–9 years and remains constant throughout life. COPD patients had similar levels and avidity of RSV-specific IgG antibodies compared with age-matched healthy controls. Conclusions: RSV-IgG antibody patterns throughout life can be used to estimate the degree of immunity acquisition to RSV and to identify groups at increased risk of infection. Seroprevalence of IgA could be a proxy to determine RSV infection in children younger than 1 year. Abstract : RSV-IgG antibody patterns throughout life can be used to estimate the degree of immunity to RSV and identify groups at increased risk of infection while IgA seroprevalence could be used as proxy for RSV infection in children < 1 year.